Biomass, production and growth strategies of the eelgrass Zostera marina, a relict cold-loving species: the Venice Lagoon as a study case - Sfriso, Adriano; Buosi, Alessandro; Tomio, Yari; Silan, Giulia; Wolf, Marion Adelheid; Sciuto, Katia; Sfriso, Andrea Augusto (Frontiers in Marine Science, 2024)
This study investigates the biomass production and growth strategies of the relict seagrass Zostera marina, a species sensitive to high temperatures, within the Venice Lagoon (Italy). Monthly data collected from January to December 2019 and November 2020 to October 2021 in a single station in proximity of one lagoon port-entrance, along with seasonal data from 2018 and 2021 for the whole lagoon, were analyzed in conjunction with environmental parameters and macroalgal presence. The objective was to understand the impact of climate changes, particularly rising water temperatures, on the cover, standing crop and net primary production of Z. marina and the effect of the MoSE gate closures designed to protect Venice from high-water events. Despite expectations of a decline due to temperature increase and reduced water exchange, our findings reveal a notable adaptability of Z. marina, with increases in both cover and biomass. This resilience suggests that Z. marina can counteract environmental challenges, making this study relevant for broader ecological and conservation contexts beyond the Venice Lagoon.